Water Splitting Induced by Visible Light at a Copper‐Based Single‐Molecule Junction. Issue 28 (4th June 2021) - Fukuzumi, Risa; Buerkle, Marius; Li, Yu; Kaneko, Satoshi; Li, Peihui; Kobayashi, Shuji; Fujii, Shintaro; Kiguchi, Manabu; Nakamura, Hisao; Tsukagoshi, Kazuhito; Nishino, Tomoaki
Abstract: Water splitting is an essential process for converting light energy into easily storable energy in the form of hydrogen. As environmentally preferable catalysts, Cu‐based materials have attracted attention as water‐splitting catalysts. To enhance the efficiency of water splitting, a reaction process should be developed. Single‐molecule junctions (SMJs) are attractive structures for developing these reactions because the molecule electronic state is significantly modulated, and characteristic electromagnetic effects can be expected. Here, water splitting is induced at Cu‐based SMJ and the produced hydrogen is characterized at a single‐molecule scale by employing electron transport measurements. After visible light irradiation, the conductance states originate from Cu/hydrogen molecule/Cu junctions, while before irradiation, only Cu/water molecule/Cu junctions were observed. The vibration spectra obtained from inelastic electron tunneling spectroscopy combined with the first‐principles calculations reveal that the water molecule trapped between the Cu electrodes is decomposed and that hydrogen is produced. Time‐dependent and wavelength‐dependent measurements show that localized‐surface plasmon decomposes the water molecule in the vicinity of the junction. These findings indicate the potential ability of Cu‐based materials for photocatalysis. Abstract : Water splitting is achieved via visible‐light irradiation on a copper‐based single‐molecule junction, which allowed the detection of chemical reactants at the smallest scale possible. The electric current measurements and inelastic electron tunneling spectroscopy distinguish the produced hydrogen from the water molecule and characterized the junction structure with the support of the first‐principles transport calculations based on the density functional theory.